Ensino, pesquisa, extensão: Contribuições da pesquisa-ação / Enseñanza, investigación y extensión: Contribuciones de la investigación-acción - Campos, Elisabete Ferreira Esteves (Universidad de Costa Rica, 2020)
This essay discusses critical action research as a fruitful path for dialogue between university and elementary school, considering the indissociability teaching-research-extension. The epistemological principles formulated by Thiollent, Monceau and Franco, which characterize action-research as a formative and intervention research, are appropriate, especially at the present time when the various forms of disqualify the emancipatory education reach the Brazilian education institutions, endangering the university as a place for debate, theoretically grounded. With the theoretical support of Freire, it is proposed the construction of critical thinking about Brazilian educational scenario, from the dialogue between university and elementary school, expanding the dialogues about educational polices.